Have Diminishing Returns Set in? The Efficiency of Indonesian Tax Administration - Iswahyudi, Heru (UI Scholars Hub, 2020)
This article aims to determine whether Indonesia’s tax administration operates at diminishing returns to scale. The neoclassical growth model was employed to measure the tax administration’s Total Factor Productivity (TFP), which may represent the level of efficiency. A low level of TFP could indicate that an organization may be inefficient and thus may operate at diminishing returns to scale. Results show that the TFP of Indonesia’s tax administration is basically nonexistent, and the diminishing returns to scale might have set in its operations. Left unchanged, these conditions may imply some future limits to tax revenue expansions. Simplifying the tax system, changing tax officials’ attitudes toward taxpayers, and improving the information system management and the business practices could be considered to increase the efficiency of tax administration. Maintaining the stability of tax legislations and overcoming organizational path dependencies could also be considered.